If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + -2f = 8 + -6f Solving -8 + -2f = 8 + -6f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '6f' to each side of the equation. -8 + -2f + 6f = 8 + -6f + 6f Combine like terms: -2f + 6f = 4f -8 + 4f = 8 + -6f + 6f Combine like terms: -6f + 6f = 0 -8 + 4f = 8 + 0 -8 + 4f = 8 Add '8' to each side of the equation. -8 + 8 + 4f = 8 + 8 Combine like terms: -8 + 8 = 0 0 + 4f = 8 + 8 4f = 8 + 8 Combine like terms: 8 + 8 = 16 4f = 16 Divide each side by '4'. f = 4 Simplifying f = 4
| x^2+110x+2000=0 | | -6q=q-7q | | (x+2)+(2x-3)=180 | | 5r=1+5r | | 3x+5y(2x-2)=16 | | 6j=-9+5j | | 3*(2-b)=4b-[5b+1-3*(5-2b)] | | -10+2t=-8t+10 | | 7y(8y+3)= | | 2+ln(2x-5)=2.5 | | 4h+2=4h | | 21,99= | | -7v=-7v+4 | | 120-x=8x | | 40-x=2x | | 2(-3y+7)-3y=14 | | -6b-1=-6b | | 60-x=4x | | 50-x=4x | | 30-x=4x | | -5g=-2g-3g | | (x-2)2=(x+6)2 | | 4p-9=-9-7p | | -2y+3=-2y | | 15-8x=4x+7 | | -3m-10=-10-3m | | 3x-12x+7=6 | | 3z+y= | | 2x-3=40-1x | | 2n=8+10n | | 3y+3-4y=0 | | (5x-1)(x+2)=8x-4 |